Projeto de antenas para dispositivos multimédia - Albino Miguel Soares Alves (2018)
Nowadays people are becoming more accustomed to being in constant contact with multimedia devices, and for many of them, the day-to-day life depends directly on multimedia devices. Thus, it is increasingly common, for example, to see people on a phone call in the middle of traffic while driving. When we sit on a motorcycle, we are accustomed to finding a dashboard that gives us some information about the state of the bike. However, we rarely find anything in the field of connectivity. It is in this field that the theme of this dissertation is inserted. The product of this dissertation will consist of an adaptation of one of the fully programmable instrument panels manufactured by Bosch Car Multimedia. One of the features of this device is to allow the driver to connect to the internet, as well as allowing a smartphone to connect to the dashboard as well as a helmet using Bluetooth® technology. Therefore, when we are driving a motorcycle it is possible to both receive calls and make calls to a certain person. At present, these features are implemented using chip antennas, which typically have poor performance and have a non-negligible cost. Therefore, the introduction of antennas printed on the printed circuit board with a central frequency of operation at 2.45Ghz with a bandwidth of 2.4Ghz to 2.5Ghz will be analyzed. Initially, the original chip antennas will be tested, subsequently, novel antennas will be developed and simulated in HFSS as well as manufactured and characterized in the anechoic chamber in order to evaluate the possibility of using these antennas on future products.